Individual approach as a means of forming the intellectual culture of students (Pedagogy of Higher and Secondary Education, 2011)
In the article the interpretation of the basic concept of the subject, analyzed the students’ intellectual culture of illustrates the key ways of its formation.
Keywords: students; individual approach; culture; intellectual culture